2005
DOI: 10.1590/s1517-86922005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento físico como modulador positivo nas alterações no eixo neuroimunoendócrino em indivíduos com insuficiência cardíaca crônica: possível atuação do fator de necrose tumoral-alfa

Abstract: O exercício físico crônico ou o treinamento físico (TF) tem sido largamente utilizado nos últimos anos com finalidade terapêutica e preventiva em uma série de condições fisiopatológicas, incluindo doenças cardiovasculares. Além dos benefícios cardiovasculares, o TF modula a expressão elevada de citocinas pró-inflamatórias, atuando sobre o eixo neuroimunoendócrino. Atualmente, o quadro de insuficiência cardíaca crônica (ICC) tem sido reconsiderado como uma interação entre mecanismos hemodinâmicos, neurormonais,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(105 reference statements)
0
5
0
1
Order By: Relevance
“…treadmill exercise) contributes to maintaining the number of myenteric neurons Martinez Gagliardo et al 2008). Chronic, moderate physical exercise stimulates the immune response (Nakamura et al 2010;Soares et al 2010) and serves as a positive modulator when considering neuroimmunoendocrine changes in patients with chronic heart failure (Rosa & J unior 2005). Chronic, moderate physical exercise stimulates the immune response (Nakamura et al 2010;Soares et al 2010) and serves as a positive modulator when considering neuroimmunoendocrine changes in patients with chronic heart failure (Rosa & J unior 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…treadmill exercise) contributes to maintaining the number of myenteric neurons Martinez Gagliardo et al 2008). Chronic, moderate physical exercise stimulates the immune response (Nakamura et al 2010;Soares et al 2010) and serves as a positive modulator when considering neuroimmunoendocrine changes in patients with chronic heart failure (Rosa & J unior 2005). Chronic, moderate physical exercise stimulates the immune response (Nakamura et al 2010;Soares et al 2010) and serves as a positive modulator when considering neuroimmunoendocrine changes in patients with chronic heart failure (Rosa & J unior 2005).…”
mentioning
confidence: 99%
“…Such exercise has also been shown to be a resistance factor in the development of infections caused by protozoa in animals (Soares et al 2010;Occhi et al 2012). Chronic, moderate physical exercise stimulates the immune response (Nakamura et al 2010;Soares et al 2010) and serves as a positive modulator when considering neuroimmunoendocrine changes in patients with chronic heart failure (Rosa & J unior 2005). Research conducted in animals has revealed positive effects of chronic, moderate physical exercise (i.e.…”
mentioning
confidence: 99%
“…A reduction in plasma concentration of TNF-α, IL-6 and their receptors in soluble form have also been demonstrated in individuals with HF undergoing an aerobic training program 55 , suggesting a reduction in the chronic inflammatory condition, mediated by a regulation in peripheral inflammatory response 56,57 . However, despite the marked restorative and/or anti-inflammatory effect of exercise in these conditions, little is known about the possible mechanisms by which aerobic training can modulate this process 57 .…”
Section: Effect Of Aerobic Training On Pro-inflammatory Cytokines In Hfmentioning
confidence: 97%
“…However, despite the marked restorative and/or anti-inflammatory effect of exercise in these conditions, little is known about the possible mechanisms by which aerobic training can modulate this process 57 .…”
Section: Effect Of Aerobic Training On Pro-inflammatory Cytokines In Hfmentioning
confidence: 99%
“…O treinamento físico moderado exerce um efeito positivo nas variáveis cardiocirculatórias, atua como um importante imunomodulador positivo, revertendo, mesmo que de maneira parcial, as alterações inflamatórias decorrentes do quadro de insuficiência cardíaca, reforçando seu papel de intervenção não farmacológica reduzindo, assim, os seus sintomas (9,10).…”
Section: Materiais E Métodosunclassified